The Violence in Tunisia during the French colonization - Ramzi Tej (Social Empowerment Journal, 2021)
The present research paper seeks to come up with a common definition to the phenomenon of violence. It mainly emanates from the complexity of the terminology in itself, which is due to the multitude of theses that have dealt with this concept from distinct sociological, anthropological and historical perspectives. Besides, the phenomenon of violence has serious repercussions on individuals. The latter are viewed as victims and stigmatized people who commit violence against customs and laws.To achieve these aims, this research follows a scientific and rigorous approach, which is based on a historical method. The latter determines the historical aspects of the origins of violence as well as the reasons for its widespread since the late 19th century until the mid – 1960’s. This paper also relies on the use of descriptive approach to depict all the relevant details related to violence. The principle of complementarity between the two approaches is guaranteed.  Going beyond the controversy caused by former scholars, the study highlights the difficulty of arriving at a linguistic and a standardized definition of violence as opposed to the presence of some conformity in its overall terminological aspects. It presents a number of implications on the phenomenon of violence such as the creation of perverts and more stigmatized individuals despite the undertaken coercive measures.